Small-Sample Machine Learning-Based Prediction of Ignition Delay Times for NH3-H2 blends - Chen Wang; Zhan Si; Yanrong Peng; Tingting Wang; Deguang Liu; Haiqiao Wei; Jiaying Pan; Haizhu Yu; Yao Fu (Fuel, 2026)

An automated and high-throughput approach to profile betaine lipids in microalgae - Yanrong Li; Tong Mu; Zhujun Zhu; Yuanyuan Fu; Jilin Xu; Xiaojun Yan (Algal Research, 2026)

Accurate detection and high throughput profiling of unknown PFAS transformation products for elucidating degradation pathways - Bei Zhang; Jibao Liu; Shanshan Qing; Thilini Maheshika Herath; Huan Zhao; Supaporn Klabklaydee; Qing-Long Fu; Eunsang Kwon; Nozomi Takeuchi; Douyan Wang; Takao Namihira; Toshihiro Isobe; et al. (Water Research, 2025)

Reforestation practices have varied the resilience of nosZ-type denitrifier communities: A 40-year soil chronosequence study - Haoyan Xiao; Hanxia Yu; Juntao Wang; Lulu He; Zhenyu Wang; Yanrong Fu; Xiaohua Wan; Jason K. Reynolds; Zhiqun Huang (Applied Soil Ecology, 2025)

Characterization of a short-term processing technology of black garlic with low 5-HMF content - Jun Liu; Jing Li; Shihao Ge; Xiaoyu Fu; Jiamin Zhu; Mengnan Wang; Yanrong Wang; Xiaoxiao Huang; Xinzheng Qin; Yixian Tu; Jun Xing; Chao Ma; et al. (Food Control, 2024)

Genotoxicity and cytotoxicity evaluation of a heat-not-burn product - Fudong Fu; Xiaoyu Li; Younan Chen; Lan Li; Jiexiong Dou; Kun Liang; Yexian Chen; Yanrong Lu; Yuchuan Huang (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Enhanced reduction of sulfate by iron-carbon microelectrolysis: interaction mechanism between microelectrolysis and microorganisms - Hanzhe Li; Junzhen Di; Yanrong Dong; Sihang Bao; Saiou Fu (Environmental Science and Pollution Research, 2024)

Trophic interactions in soil micro‐food webs drive ecosystem multifunctionality along tree species richness - Xiuzhen Shi; Nico Eisenhauer; Josep Peñuelas; Yanrong Fu; Jianqing Wang; Yuxin Chen; Shengen Liu; Lulu He; Manuel Esteban Lucas‐Borja; Liyan Wang; Zhiqun Huang (Global Change Biology, 2024)
Rapid biodiversity losses under global climate change threaten forest ecosystem functions. However, our understanding of the patterns and drivers of multiple ecosystem functions across biodiversity gradients remains equivocal. To address this important knowledge gap, we measured simultaneous responses of multiple ecosystem functions (nutrient cycling, soil carbon stocks, organic matter decomposition, plant productivity) to a tree species richness gradient of 1, 4, 8, 16, and 32 species in a young subtropical forest. We found that tree species richness had negligible effects on nutrient cycling, organic matter decomposition, and plant productivity, but soil carbon stocks and ecosystem multifunctionality significantly increased with tree species richness. Linear mixed‐effect models showed that soil organisms, particularly arbuscular mycorrhizal fungi (AMF) and soil nematodes, elicited the greatest relative effects on ecosystem multifunctionality. Structural equation models revealed indirect effects of tree species richness on ecosystem multifunctionality mediated by trophic interactions in soil micro‐food webs. Specifically, we found a significant negative effect of gram‐positive bacteria on soil nematode abundance (a top‐down effect), and a significant positive effect of AMF biomass on soil nematode abundance (a bottom‐up effect). Overall, our study emphasizes the significance of a multitrophic perspective in elucidating biodiversity‐multifunctionality relationships and highlights the conservation of functioning soil micro‐food webs to maintain multiple ecosystem functions.

Adsorption mechanism of phosphorus on biomass ash modified with lanthanum immobilized by chitosan - Yangyang Jiang; Junzhen Di; Yiming Ma; Saiou Fu; Yanrong Dong; Bofu Yuan (Environmental Science and Pollution Research, 2023)

Residential greenness and dyslipidemia risk: Dose-response relations and mediation through BMI and air pollution - Qinjian Wang; Xiaoqing Li; Wenling Zhong; Hongyun Liu; Chuanteng Feng; Chao Song; Bin Yu; Yao Fu; Xi Lin; Yanrong Yin; Tiehui Chen; Jan D. Reinhardt; et al. (Environmental Research, 2023)

Preparation of lignite-loaded nano-FeS and its performance for treating acid Cr(VI)-containing wastewater - Saiou Fu; Junzhen Di; Xuying Guo; Yanrong Dong; Sihang Bao; Hanzhe Li (Environmental Science and Pollution Research, 2023)

MicroRNA-375 overexpression disrupts cardiac development of Zebrafish (Danio rerio) by targeting notch2 - Sisi Zhuang; Yanrong Fu; Jingyun Li; Mengmeng Li; Xiaoshan Hu; Jingai Zhu; Meiling Tong (Protoplasma, 2020)